Pengembangan Panduan Numerasi Transisi Paud-SD Yang Menyenangkan Untuk Kesiapan Bersekolah - Nova Liana; Eka Sastrawati; Hendra Budiono (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
The transition from Early Childhood Education (ECE) to Primary School is a critical phase that determines children’s school readiness, particularly in the aspect of numeracy. However, mathematics learning in early primary grades is still predominantly centered on textbooks and lecture-based methods, making it less engaging and insufficiently aligned with students’ developmental characteristics. This study aims to develop an enjoyable numeracy transition guide from ECE to primary school to support the school readiness of first-grade students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were first-grade students at SD Negeri 80/I Muara Bulian. Data were collected through interviews, questionnaires, and observations, while data analysis was conducted using descriptive quantitative and qualitative approaches. The results indicate that the developed numeracy guide was rated as highly valid by media and content experts, valid by language experts, and highly practical based on teachers’ and students’ responses. Therefore, the developed ECE–primary school numeracy transition guide is feasible to be used as an alternative instructional material to create enjoyable learning experiences and support the school readiness of early primary students.